Improving depressive symptoms and maintaining cognitive abilities of seniors within the nursing homes: A pilot study of brief mindfulness-based interventions for seniors in a semi-randomized trial - Aisenberg-Shafran, Daniela; Harmatz, Margalit (Frontiers in Psychology, 2023)
Seniors in nursing homes are at higher risk for depression and emotional distress. The COVID-19 crisis and isolation have even increased the risk for cognitive decline and suicidality. Since social media is often unfamiliar to older adults, their treatment options were diminished during quarantine. Recently, studies showed the potential for Mindfulness-Based Intervention in improving cognitive functioning and psychological well-being among healthy elderly. Standardized courses such as MBSR and MBCT are not suited to the majority of seniors for several reasons. First, the interventions are too long and demanding, physically and cognitively. Second, they require an instructed counselor for delivery, which makes it almost impossible in times of quarantine, and third, very expensive in regular days. Hence, the purpose of this study was to examine whether similar improvements in emotional distress and cognitive functioning can be achieved through a brief intervention, that can be delivered by workers in nursing homes. A course of 8 half-hour sessions each (MBIS: Mindfulness-Based Intervention for Seniors) was employed in two versions: 1) An 8-week course with weekly meetings 2) A 4-week course that with 2 sessions per week and compared to a control care-as-usual group. Depression and mood were measured, as well as cognitive abilities in the Simon's task. In addition, the level of Mindfulness skills was measured before and after the interventions. Results showed that brief interventions succeeded in improving mindfulness Non-reactivity and produced change in Acting with awareness and Non-judging facets. More importantly, the brief intervention, in both frequency versions, improved the level of depression and mood (BDI and PHQ-9). At the cognitive level, an adaptive sequential effect appeared after the intervention only in the 8-week MBIS group. These findings indicate the effectiveness of this pilot of a short, simple, mindfulness-based intervention, in improving depression and psychological distress, as well as improving cognitive control over time. This may enhance significant developments in the field of treatment solutions for seniors, with a ready-to use protocol to administer in nursing homes.